Lineage structure and penicillin-binding protein variability in clinical Streptococcus pneumoniae isolates from Southwest China exhibiting reduced susceptibility to penicillin - Chenglin Miao; Ziyi Yan; Li Liu; Xin Huang; Yingying Li; Linghan Kuang; Xingxin Liu; Jiaji Ling; Jingjing Luo; Huilian Chen; Xiaocui Huang; Xinghua Zhu; et al. (Frontiers in Public Health, 2026)
Background Reduced susceptibility to penicillin in Streptococcus pneumoniae is mediated primarily by alterations in penicillin-binding proteins (PBPs) and often coexists with multidrug resistance within successful lineages. The region-specific genomic characterization of clinically relevant pneumococci with reduced penicillin susceptibility in Southwest China remains limited. Methods We performed whole-genome sequencing of 204 clinical S. pneumoniae isolates collected from five institutions in Southwest China (2018–2022) that met our operational screening definition of reduced susceptibility to penicillin (PEN MIC ≥0.12 μg/mL). Molecular serotypes, MLST types, and Global Pneumococcal Sequence Clusters (GPSCs) were assigned; virulence and antimicrobial resistance determinants were profiled; and a core genome phylogeny was reconstructed with international contextualization through the use of PubMLST genomes meeting the same MIC criterion. Amino acid variability in PBP1a/PBP2b/PBP2x was quantified using TIGR4 numbering, and highly variable noncatalytic residues located within 15 Å of catalytic motifs were prioritized via structure-guided screening. Results The isolates showed a high burden of resistance to non-β-lactam antibiotics (erythromycin, 98.5%; tetracycline, 82.8%; trimethoprim–sulfamethoxazole, 64.7%), while fluoroquinolone susceptibility was largely preserved (≥97%), and vancomycin/linezolid resistance was not detected. Twenty-seven serotypes were identified, among which 19F (23.5%) and 19A (14.2%) were dominant, and the estimated PCV13 coverage was 69.6%. GPSC1 was the dominant lineage (36.8%), and the lineage composition among our isolates differed markedly from those in the PubMLST-USA and PubMLST-Thailand subsets. Virulence and resistance gene carriage differed markedly between GPSC1 and non-GPSC1 isolates, with enrichment of pilus operons, mef(A)/msr(D) , and folA/folP in GPSC1. PBP variations were clustered in transpeptidase domains and motif-adjacent regions while essential catalytic residues were conserved; with the structure-guided filter, 12, 11, and 11 motif-proximal noncatalytic candidate sites were prioritized in PBP1a, PBP2b, and PBP2x, respectively. Conclusion Clinical S. pneumoniae isolates with reduced penicillin susceptibility collected in Southwest China demonstrated resistance and accessory gene profiles that were strongly structured by a GPSC-defined lineage background. Our site-resolved, structure-guided PBP analysis provides a regional PBP variability landscape and a compact set of recurrent motif-proximal candidate substitutions to support surveillance and downstream functional validation.